A computer simulation for economical order picker routing when considering travel distance and vehicle energy consumption - Rojanapitoon, Theerawat; Teeravaraprug, Jirarat (International Journal of Engineering and Technology, 2018)
Order picking process is considered to be costly processes since takes long processing time and uses a lot of movements. This paper pre-sents a simulation software that utilizes multi-objective mathematical model with a consideration of travel distance and vehicle energy con-sumption. A block stacking warehouse or parallel aisle warehouse is considered in this research and only one picker with his vehicle is utilized. Optimal results of example problems are validated and verified. Finally, conclusion and discussion are given.Â Â